The Value Relevance of Accounting Information and its Impact on Stock Prices: A Study on Listed Pharmaceutical Companies at Dhaka Stock Exchange of Bangladesh - Hossain, Tarik (Journal of Asian Business Strategy, 2021)
This study intends to determine the Value relevance of accounting information (VRAI) that emphasizes the impact of different information produced by accounting on the market price of the share. This paper tries to determine the VARI on pharmaceutical companies’ share price at the Dhaka Stock Exchange (DSE) of Bangladesh. For this purpose, I have collected data from different Pharmaceutical companies listed under the DSE for the period starting from 2017 to 2019. In this study correlation, ANOVA and regression analysis are applied to ascertain the association between Financial Accounting Information like Earnings per Share (EPS); Net Operating Cash Flow Per Share (NOCFPS); Net Asset Value Per Share (NAVPS); Cash Dividend Per Share (CDPS), and Stock Dividend Per Share (SDPS) and Market Value Per Share (MVPS). The results confirmed a statistically significant positive relationship of NOCFPS, NAVPS with MVPS. Differently, the results also confirmed a statistically significant negative relationship between EPS and MVPS. The results also ascertained that CDPS, and SDPS have no significant but positive relationship with MVPS. Finally I concluded that the information produced by accounting systems are value relevance and important in decision making. The existing literature of VRAI will enrich by results of this study. This study recommends the existing and potential investors to use accounting information for taking efficient and effective investment decisions.